Impact of Cooperative Learning Approach on Students’ Achievement in Mathematics - Roka, Jasbir; Khatri, Tilak Bahadur (Journal of Educational Research and Innovation, 2024)
Cooperative Learning Approach (CLA), focusing on the collaborative, active engagement and group working to each other in mathematics learning, makes significant impact on the students' achievement in their academic career. The objective of this study is to investigate the impact of CLA on academic achievement in mathematics at grade nine students of Rukum (West), District, Nepal. A quantitative method and a quasi-experimental research design were employed in this study to examine how CLA made an impact on students in two community-based schools. The two schools were purposely selected from two strata such as one experimental stratum (N=15) and another control stratum (N=15) assigned by result of pre-test result through random selection. Mathematical Achievement Test (MAT) and participants' observation dairy notes were used as tools for data collection. The research process based on Input, Process, and Output (IPO) model whereas experimental group was taught by using CLA and control group was taught by Conventional Teaching Approach (CTA) with twenty-six days on the topic of mensuration of compulsory mathematics. At the end of intervention, post-test was administered on both groups, while the daily reflective notes prepared during intervention period among two groups related with students' learning behavior and activities regularly. The result is analyzed by using t-test to compare mean score of posttest for both groups. The result indicated significant association between mean achievements of experimental group and control group, p<0.05 that implies cooperative learning group performed better in mathematics achievement. Findings is that CLA was significantly motivated, engaged, shared, cooperative, and accountable approach than conventional approach in terms of learning concepts and skills in mathematics. The cooperative learning approach is more beneficial in mathematics teaching to enhance students' academic achievement, and therefore mathematics teachers would incorporate this approach in their teaching learning process.